Annotation: Neurofeedback - train your brain to train behaviour - Heinrich, Hartmut; Gevensleben, Holger; Strehl, Ute (Journal of child psychology and psychiatry, 2007)
Background:  Neurofeedback (NF) is a form of behavioural training aimed at developing skills for self‐regulation of brain activity. Within the past decade, several NF studies have been published that tend to overcome the methodological shortcomings of earlier studies. This annotation describes the methodical basis of NF and reviews the evidence base for its clinical efficacy and effectiveness in neuropsychiatric disorders. Methods:  In NF training, self‐regulation of specific aspects of electrical brain activity is acquired by means of immediate feedback and positive reinforcement. In frequency training, activity in different EEG frequency bands has to be decreased or increased. Training of slow cortical potentials (SCPs) addresses the regulation of cortical excitability. Results:  NF studies revealed paradigm‐specific effects on, e.g., attention and memory processes and performance improvements in real‐life conditions, in healthy subjects as well as in patients. In several studies it was shown that children with attention‐deficit hyperactivity disorder (ADHD) improved behavioural and cognitive variables after frequency (e.g., theta/beta) training or SCP training. Neurophysiological effects could also be measured. However, specific and unspecific training effects could not be disentangled in these studies. For drug‐resistant patients with epilepsy, significant and long‐lasting decreases of seizure frequency and intensity through SCP training were documented in a series of studies. For other child psychiatric disorders (e.g., tic disorders, anxiety, and autism) only preliminary investigations are available. Conclusions:  There is growing evidence for NF as a valuable treatment module in neuropsychiatric disorders. Further, controlled studies are necessary to establish clinical efficacy and effectiveness and to learn more about the mechanisms underlying successful training.